2021
DOI: 10.1038/s41598-020-80598-2
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study: effectiveness of local injection of autologous platelet-rich plasma in treating women with stress urinary incontinence

Abstract: The study aims to evaluate the effectiveness of local injection of autologous platelet rich plasma (A-PRP) as a treatment for women suffering from stress urinary incontinence (SUI). In a prospective intervention study, twenty consecutive women suffering from SUI were treated with A-PRP injection at anterior vaginal wall where mid-urethra locates. Self-reported questionnaires were used to measure pre-treatment, 1 month and 6 months post-treatment symptom severity. Secondary outcomes of sexual function and treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…And only 5 cases not improved in grade of severity of incontinence with percentage of 16.7 % of the cases as shown in Table .9. In agreement to our work, a study done by Long, et al, (2021) [13] that aimed to estimate the efficacy of regional injection of autologous platelet rich plasma (A-PRP) as a handling for females suffering from stress urinary incontinence (SUI). In this potential intervention trial, 20 consecutive females suffering from SUI were cured with A-PRP injection at the frontal vaginal wall where mid-urethra is located; their average age was 44.5 years old, with 1.6 times average parity and a BMI of 22.7 mg/m2.…”
Section: Figure (1)supporting
confidence: 79%
“…And only 5 cases not improved in grade of severity of incontinence with percentage of 16.7 % of the cases as shown in Table .9. In agreement to our work, a study done by Long, et al, (2021) [13] that aimed to estimate the efficacy of regional injection of autologous platelet rich plasma (A-PRP) as a handling for females suffering from stress urinary incontinence (SUI). In this potential intervention trial, 20 consecutive females suffering from SUI were cured with A-PRP injection at the frontal vaginal wall where mid-urethra is located; their average age was 44.5 years old, with 1.6 times average parity and a BMI of 22.7 mg/m2.…”
Section: Figure (1)supporting
confidence: 79%
“…Women with SUI who received PRP injections achieved a slightly higher treatment success rate, as defined by cure and improved symptoms, in the younger group [ 13 ]. The results herein and from our previous studies are not concurrent with previous findings in the reported literature, as the influence of age on clinical outcomes was not significant [ 12 , 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2016, the potential role of PRP in treating SUI was first proposed [ 9 ] and was applied in an animal model in 2019, in which a significant increase in leak point pressure was observed [ 10 ]. Based on the hypothesis that deficient urethral sphincter function improves following regenerated innervation and increased striated muscle cell volume via repeated PRP urethral sphincter injections, several recent studies have shown the safety and therapeutic efficacy of autologous PRP urethral sphincter injections for the treatment of SUI in humans [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…They found that PRP treatment is effective in relieving SUI symptoms without significant adverse reactions at both 1 month and 6 month follow up. PRP is also used as an adjunct therapy along with energy-based devices procedures to enhance the efficacy of the treatment [30] . In another study by Willison F et al 2021, feasibility, safety, and efficacy of FxCO 2 (Fractional Microablative CO 2 ) vaginal laser treatment and PRP was evaluated in 62 women with refractory urge urinary incontinence (UUI) with urinary function and sexual function as secondary outcome measures.…”
Section: Figure 1: the Separation Of Blood Into Three Layers After Centrifugation While Prp Preparationmentioning
confidence: 99%